1997
DOI: 10.1055/s-2007-1023093
|View full text |Cite
|
Sign up to set email alerts
|

Prognostische Bedeutung des Tumorzellnachweises im Knochenmark im Vergleich zum Nodalstatus beim primären Mammakarzinom

Abstract: Prognostische Bedeutung des Tumorzellnachweises im Knochenmark im Vergleich zum Nodalstatus beim primären Mammakarzinom Z.. wom..... nluwng: o.r lympt.knot~1n gi lt doouftt ak wl< hligsl~r prognoslischt'l" Einle.JIaktor bt-im prirnJt.., "". mnuk. rli.-... Troll~erleiden Z5 •30" der ...,o.1"""}Iliwn P. t ie'nUn...., in"f'fh. lb wn 10 Ja hr.., e;n f~ft'lIdly. [ !o>e AI I~r • n. t iv<:' l u m lymphknol~nslalus kÖflnt~d er N~h_is mikro,,*" lasl. tische. Zell.., Im KnochE'nnurk S(' in. Im Gtogerluu l u. n• de ....n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Numerous studies have shown that patients with positive tumor cell detection in the BM have a worse prognosis when compared to patients with a negative aspirate. Numerous single center studies ranging from 350 to over 800 patients with a median follow-up of up to 12 years have shown the prognostic significance of a Comparison of positivity rates between SD, PR, PD und CR: P = 0.32 b Comparison of positivity rates poor responder versus responder P = 0.11 c Comparision of positivity rates between CR and poor responders P = 0.07 d pathologic complete remission (pCR) e includes clinical complete remission with pathologic residual disease DTCs [20][21][22][23][24]. A recent pooled analysis including more than 4,700 patients confirmed these findings [14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that patients with positive tumor cell detection in the BM have a worse prognosis when compared to patients with a negative aspirate. Numerous single center studies ranging from 350 to over 800 patients with a median follow-up of up to 12 years have shown the prognostic significance of a Comparison of positivity rates between SD, PR, PD und CR: P = 0.32 b Comparison of positivity rates poor responder versus responder P = 0.11 c Comparision of positivity rates between CR and poor responders P = 0.07 d pathologic complete remission (pCR) e includes clinical complete remission with pathologic residual disease DTCs [20][21][22][23][24]. A recent pooled analysis including more than 4,700 patients confirmed these findings [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 4 samples determined to be positive by IMS-RT-PCR turned out to be negative when RT-PCR was used alone. Currently, immunocytochemistry is the routine method for diagnosing micrometastases (Diel et al 1992(Diel et al , 1997. In addition, we compared the results of these 26 samples by immunocytochemical staining using the cytospin technique with the mAb 5D3 against CK8,18,19.…”
Section: Discussionmentioning
confidence: 99%
“…Die niedrige Proliferationsaktivität der disseminierten Tumorzellen könnte verantwortlich für die Persistenz nach adjuvanter Chemotherapie sein[36]. Allerdings wurde die klinische Bedeutung der Tumorzelldissemination sowohl mit Muzin-Antikörpern als auch mit Zytokeratin-Antikörpern gleicherweise nachgewiesen[26,31,32,34,35].Solomayer E-F et al Tumorzelldissemination unter neoadjuvanter ¼ Geburtsh Frauenheilk 2003; 63: 1267 ± 1273 Die Detektion disseminierter Tumorzellen liefert keine Information über deren metastatisches Potenzial. Hingegen konnten bei 90 % (18 von 20 Frauen) der Patientinnen ohne Tumorzelldissemination vor pCHT auch nach neoadjuvanter Therapie keine gestreuten Zellen nachgewiesen werden können.Im Gegensatz zur pCHT kommt es nach adjuvanter Chemotherapie zu einer Reduktion der Tumorzelldissemination.…”
unclassified